2013
DOI: 10.1007/s00213-013-3189-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SKF-83566 and haloperidol on performance on progressive ratio schedules maintained by sucrose and corn oil reinforcement: quantitative analysis using a new model derived from the Mathematical Principles of Reinforcement (MPR)

Abstract: RationaleMathematical models can assist the interpretation of the effects of interventions on schedule-controlled behaviour and help to differentiate between processes that may be confounded in traditional performance measures such as response rate and the breakpoint in progressive ratio (PR) schedules.ObjectiveThe effects of a D1-like dopamine receptor antagonist, 8-bromo-2,3,4,5-tetrahydro-3-methyl-5-phenyl-1H-3-benzazepin-7-ol hydrobromide (SKF-83566), and a D2-like receptor antagonist, haloperidol, on rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 86 publications
9
7
1
Order By: Relevance
“…In Experiment 2, we validated our PR task by showing that the breakpoint could be increased (i.e., from approximately 35 to 60) by conditions classically considered motivators of appetitive behavior – e.g., food-deprivation. While higher breakpoints and/or mean cumulative responses have been observed in other studies [e.g., 31 , 36 , 37 ] the ones reported in the present study are still consistent with other reports [e.g., 30 , 38 ]. While it was somewhat surprising that breakpoints for Ensure decreased from presurgical to postsurgical conditions in the SHAM rats from both diet groups, this could potentially be attributed to the long span of time between test phases (at least 3 weeks) and that postsurgical testing was not immediately preceded by training.…”
Section: Discussionsupporting
confidence: 93%
“…In Experiment 2, we validated our PR task by showing that the breakpoint could be increased (i.e., from approximately 35 to 60) by conditions classically considered motivators of appetitive behavior – e.g., food-deprivation. While higher breakpoints and/or mean cumulative responses have been observed in other studies [e.g., 31 , 36 , 37 ] the ones reported in the present study are still consistent with other reports [e.g., 30 , 38 ]. While it was somewhat surprising that breakpoints for Ensure decreased from presurgical to postsurgical conditions in the SHAM rats from both diet groups, this could potentially be attributed to the long span of time between test phases (at least 3 weeks) and that postsurgical testing was not immediately preceded by training.…”
Section: Discussionsupporting
confidence: 93%
“…Given that 5-HT 2C Rs are also expressed in the VTA (Bubar and Cunningham, 2007; Bubar et al , 2011), a brain region associated with food and drug reward (DiLeone et al 2012), we investigated lorcaserin’s effects on a PR schedule using a mathematical model (Bradshaw and Killeen, 2012) derived from Killeen’s Mathematical Principles of Reinforcement (MPR, Killeen 1994). In agreement with previous reports in rats (Bezzina et al , 2015; Bradshaw and Killeen, 2012; Olarte-Sanchez et al , 2013, 2015; Valencia-Torres et al , 2014) our results indicate that operant behavior maintained by PR schedules is well described by the mathematical model in mice (Bradshaw and Killeen, 2012). Progressive ratio schedules are widely used to assess the effects of neuropharmacological interventions on motivation.…”
Section: Obesity Medication Lorcaserin Reduces Food Intake and Operansupporting
confidence: 93%
“…Consistent with the notion that a is an index of incentive value, it has been found that this parameter is monotonically related to the volume of a sucrose-solution reinforcer ( Rickard et al, 2009 : data re-analysed by Bradshaw and Killeen, 2012 ). Recently, Olarte-Sánchez et al (2013) compared the values of a for corn oil and sucrose reinforcers; their findings were consistent with extant evidence that sucrose is less efficacious than corn oil on a volume-for-volume basis, but more efficacious on a calorie-for-calorie basis ( Naleid et al, 2008 ). Valencia-Torres et al (2014) found that diabetes induced by systemic treatment with streptozotocin was associated with a reduction of a , consistent with an antihedonic effect of this treatment ( Nefs et al, 2012 ).…”
Section: Introductionsupporting
confidence: 60%